Large-Scale Enterprise in the Light of Income Tax Returns - Crum, W. L. (Quarterly Journal of Economics, 1933)
Purposes of the investigation, 414. — Description of the data, 416. — Importance of the consolidated returns, 419. — Profit ratios: divisions, 433. — Profit ratios: manufacture groups, 439. — Rate of profit on gross sales, 443. — General conclusion, 445.